Experimental investigation on mechanical properties of FFF parts using different materials - Djokikj, Jelena; Doncheva, Elisaveta; Tuteski, Ognen; Hadjieva, Bojana (ELSEVIER B.V., 2022)
Fused filament fabrication (FFF) is one of the additive manufacturing processes that provides parts with finest mechanical properties. Different materials offer different mechanical properties of the part. In this research we investigated parts fabricated with polylactic acid (PLA), polycarbonate (PC) and polyethylene terephthalate glycol, PETG. Samples are designed according to the ASTM standards and fabricated under the same process parameters. The mean effect on the tensile strength and flexural strength have been studied. From the study it can be concluded that there is a difference in the results as expected. But we cannot say that there is one material with superior properties, simply different materials are suitable for different applications
Keywords: fused filament fabrication (FFF); tensile strength; flextural strength; test speciments; mechanical properties